The6000Project: How a Small Winery's Crisis Became a Social Media Crowdfunding Success - Damien Wilson; Réka Háros (Wine Business Journal)
In the last week of February 2020, Sfriso Winery, a small, family-owned winery in the countryside of northeastern Italy, was forced to indefinitely suspend operations as one of the first wine businesses affected by the crisis resulting from the Coronavirus pandemic. The prospect of indefinite delays affecting their traditional distribution model forced the husband and wife team of Pier Sfriso and Réka Háros to rely on innovation as a means to find new customers. With the couple predominantly relying on tourism for new client acquisition before COVID-19, the prospect of attracting enough customers via alternative means appeared daunting.